Methodology of External Costs Evaluation of Energy Production in Local System - Graczyk, Andrzej (Regional Barometer. Analyses & Prognoses, 2012)
The aim of the article is a proposed methodology of external costs evaluation with the use of a methodology based mainly on European Union research studies. The basis is the method of the impact pathway approach on advantages of incumbent environmental services introduced in the first part of article. The procedure of external costs evaluation of energy systems of communes and administrative districts is discussed in the second part, with particular regard to recommended solutions at individual stages of procedure.